Genetic epidemiology of low back pain and intervertebral disc degeneration - Williams, Frances (Henry Stewart Talks, 2018)
The problem of low back pain (LBP), Intervertebral disc degeneration, Twin studies and their contribution, Genetic studies, Candidate genes, linkage and genome-wide association, PainOmics